A BIBLIOMETRIC ANALYSIS OF RESPIRATORY TRACT INFECTION EDUCATION IN CHILDREN USING VOSVIEWER: RESEARCH TRENDS AND FUTURE DIRECTIONS - Athira Nur Fairisha; Rahmah (GoAcademica Research dan Publishing, 2026)
Acute Respiratory Tract Infection (ARTI) is one of the leading causes of morbidity and mortality among children, particularly in low- and middle-income countries. Although the number of studies related to ARTI continues to increase, comprehensive mapping of research trends on ARTI education in children remains limited. Therefore, this study aims to analyze publication trends, country contributions, citation impact, and thematic clusters in ARTI education research in children from 2020 to 2025. This study employed a bibliometric analysis using data from the Scopus database with the keywords “Acute Respiratory Tract Infection,” “Education,” and “Children.” The results indicate a consistent increase in publications during the observation period, with contributions dominated by high-income countries. Highly cited articles are generally published in high-impact journals. Network visualization identified major clusters dominated by clinical topics such as pneumonia prevention, hygiene practices, parental education, public health interventions, and rational antibiotic prescribing. Recent evidence shows that indoor air pollution significantly affects respiratory health outcomes in children (Springer, 2026). Furthermore, integrated interventions combining educational strategies with air filtration technology have been shown to reduce respiratory infections among children (KidsAIR Trial, 2022).